Baculovirus expression vector system: an emerging host for high-throughput eukaryotic protein expression. - Shrestha, B; Smee, C; Gileadi, O (2008)
The increasing demand for production and characterization of diverse groups of recombinant proteins necessitates the analysis of several constructs and fusion tags in a variety of expression systems. The challenge is to screen multiple clones quickly for the desired properties. When using a eukaryotic system, such as baculovirus-mediated expression in insect cells, the total time required and the volume of culture needed to obtain reasonable results are limiting factors. This chapter focuses on addressing these issues by describing rapid small-scale expression as a mode of screening. The method allows the rapid identification of the best clone before scaling-up and the production of heterologous protein.